SNACK PRODUCTS FROM WHOLE-GRAIN RED SORGHUM FLOUR WITH PAPRIKA AND COCOA POWDERS - Janić Hajnal, Elizabet; Banjac, Vojislav; Filipčev, Bojana; Radić, Bojana; Kos, Jovana; Šimurina, Olivera; Cvetković, Biljana (Food and Feed Research, 2024)
Among the cereals, sorghum (Sorghum bicolor L. Moench) is a member of the gluten-free cereal family. This crop is widely cultivated in a wide range of geographic locations due to its strong heat and drought resistance and high photosynthetic efficiency. Rich in macronutrients (proteins, fats, and carbohydrates) and micronutrients (minerals, vitamins), sorghum also contains phenolic compounds (tannins, phenolic acids, and flavonoids), which have antioxidant properties. Given its many health benefits, including its ability to suppress the formation of cancer cells and reduce obesity, heart disease, and diabetes, sorghum is used for both human and animal consumption. It can be used for baking, extrusion, and different cereal-based products such as bread, cookies, pasta, expanded snacks, and breakfast cereals. This study aimed to develop four types of snack products based on red sorghum flour (95, 92, 90, and 89%) with the addition of i) a mixture of sweet and hot ground red pepper (5, 8 and 10%); ii) cocoa powder (5, 8 and 10%); and iii) a mixture of cocoa powder (10%) and cinnamon (1%), while a 100% red sorghum snack product served as a control sample. The following extrusion processing parameters were used: feeding rate of 50 kg/h, screw speed of 800, 850, and 900 RPM, and the material moisture content in the extruder barrel ranged from 13 to 14%. The following quality attributes of snacks obtained were determined: expansion ratio, bulk density, water absorption index, water solubility index, colour and texture (hardness, number of fractures, crispiness work, crispiness index). Based on the selected quality indicators, all types of snack products obtained in this study have the potential for commercialization. However, before commercialization, consumer acceptance tests and preference tests need to be conducted.